Nanomaterial payload delivery to central nervous system glia for neural protection and repair - Saksena, Jayant; Hamilton, Adelle E.; Gilbert, Ryan J.; Zuidema, Jonathan M. (Frontiers in Cellular Neuroscience, 2023)
Central nervous system (CNS) glia, including astrocytes, microglia, and oligodendrocytes, play prominent roles in traumatic injury and degenerative disorders. Due to their importance, active pharmaceutical ingredients (APIs) are being developed to modulate CNS glia in order to improve outcomes in traumatic injury and disease. While many of these APIs show promise in vitro, the majority of APIs that are systemically delivered show little penetration through the blood-brain barrier (BBB) or blood-spinal cord barrier (BSCB) and into the CNS, rendering them ineffective. Novel nanomaterials are being developed to deliver APIs into the CNS to modulate glial responses and improve outcomes in injury and disease. Nanomaterials are attractive options as therapies for central nervous system protection and repair in degenerative disorders and traumatic injury due to their intrinsic capabilities in API delivery. Nanomaterials can improve API accumulation in the CNS by increasing permeation through the BBB of systemically delivered APIs, extending the timeline of API release, and interacting biophysically with CNS cell populations due to their mechanical properties and nanoscale architectures. In this review, we present the recent advances in the fields of both locally implanted nanomaterials and systemically administered nanoparticles developed for the delivery of APIs to the CNS that modulate glial activity as a strategy to improve outcomes in traumatic injury and disease. We identify current research gaps and discuss potential developments in the field that will continue to translate the use of glia-targeting nanomaterials to the clinic.